2012
DOI: 10.1029/2011ja017188
|View full text |Cite
|
Sign up to set email alerts
|

Dayside auroral emissions controlled by IMF: A survey for dayside auroral excitation at 557.7 and 630.0 nm in Ny‐Ålesund, Svalbard

Abstract: .[1] A survey of dayside 557.7 and 630.0 nm auroral emission, acquired from the all-sky imagers at the Yellow River Station in Ny-Ålesund, Svalbard, shows that the dayside auroral oval could be divided into five auroral active regions: the dawnside (Da, 06:00-07:30 MLT) and duskside (Du,(15)(16)(17):00 MLT) green aurora sectors, the prenoon (W, 07:30-10:00 MLT) and postnoon (H, 13:00-15:30 MLT) peaks for 557.7 and 630.0 nm auroral emissions, and the midday gap (M, 10:00-13:00 MLT) for green aurora. The 630.0 n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
37
0
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 27 publications
(38 citation statements)
references
References 76 publications
(116 reference statements)
0
37
0
1
Order By: Relevance
“…Since dayside chorus waves are persistent even during geomagnetically quiet conditions and show high occurrences at L > 7 (Li et al, 2009), we adopt a typical model of dayside chorus emissions at high L approximately corresponding to the field line of YRS location and the geomagnetic condition of the time, and perform a comprehensive evaluation of plasma sheet electron scattering rates by dayside chorus in realistic magnetic field models, which are subsequently used to compare with the strong diffusion limit and estimate the energy-dependent degree of loss cone filling. We demonstrate that resonant interactions with dayside lower-band chorus can lead to efficient resonant scattering of ≥500 eV to a few keV electrons (Hu et al, 2012) to substantially fill the loss cone and thus mainly contribute to the YRS ASI observed intensification of dayside green-line diffuse auroral precipitation, supporting that dayside chorus could play a major role in the production of dayside diffuse aurora.…”
mentioning
confidence: 91%
See 3 more Smart Citations
“…Since dayside chorus waves are persistent even during geomagnetically quiet conditions and show high occurrences at L > 7 (Li et al, 2009), we adopt a typical model of dayside chorus emissions at high L approximately corresponding to the field line of YRS location and the geomagnetic condition of the time, and perform a comprehensive evaluation of plasma sheet electron scattering rates by dayside chorus in realistic magnetic field models, which are subsequently used to compare with the strong diffusion limit and estimate the energy-dependent degree of loss cone filling. We demonstrate that resonant interactions with dayside lower-band chorus can lead to efficient resonant scattering of ≥500 eV to a few keV electrons (Hu et al, 2012) to substantially fill the loss cone and thus mainly contribute to the YRS ASI observed intensification of dayside green-line diffuse auroral precipitation, supporting that dayside chorus could play a major role in the production of dayside diffuse aurora.…”
mentioning
confidence: 91%
“…A recent auroral precipitation study by Newell et al (2009), developed using 11 years of particle data from the DMSP series satellites, also showed that the diffuse aurora is more intense post-midnight and into the morning hours and often relatively insignificant from post-noon through dusk, owing to the predominant eastward transport of electrons as a result of a combination of E × B and gradient drifting from the nightside plasma sheet. In contrast, Hu et al (2009Hu et al ( , 2012, using the ground-based all-sky imager (ASI) measurements at the Chinese Yellow River Station in Ny-Ålesund, Svalbard, surveyed the synoptic distribution of dayside aurora emissions and their potential correlation with the interplanetary magnetic field (IMF), indicating a pre-noon (07:30-09:30 MLT) "warm spot" characterized uniquely by an increase of 557.7 nm emissions, which is contributed by the emissions of the discrete and diffuse aurora, and a midday (09:30-13:00 MLT) gap of relatively weak green line emissions for the discrete and diffuse aurora. Miyoshi et al (2010) proposed a model for the energy dispersion of electron precipitation associated with pulsating auroras; the dynamic structure embedded the diffuse aurora, and conducted a time-of-flight (TOF) analysis of precipitating electrons observed by the REIMEI satellite which suggested that the modulation region of wave-induced pitch angle scattering is near the magnetic equator.…”
mentioning
confidence: 95%
See 2 more Smart Citations
“…The Chinese Arctic Yellow River Station (YRS) in Ny‐Ålesund, Svalbard, is located at the geographic coordinates 78.92°N, 11.93°E with the corrected geomagnetic latitude 76.24° and magnetic local time (MLT) ≈ UT + 3 h. Three identical all‐sky imagers (ASI), supplied with the narrow band interferential filters centered, respectively, at N 2 + (1NG) 427.8 nm, O (1S) 557.7 nm, and O (1D) 630.0 nm, have been in operation since November 2003. The auroras at three wavelengths are shown in blue, green, and red colors, which mainly correspond to the precipitating electrons with energies above a few keV, 0.5 to a few keV, and less than 500 eV, respectively [ Hu et al ., , ]. The ASI temporal resolution is 10 s, including a 7 s exposure time and a 3 s readout time.…”
Section: Observations and Analysesmentioning
confidence: 99%